Effect of intermittent hypercapnic gas inhalation on ventilatory response in tirathletes - Kato, T.; Sakata, Y.; Sugiura, Y.; Yamashita, N.; Tsukanaka, A.; Matsumoto, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Hypercapnic stimulation has a strong power to ventilatory response. Therefore, the application of hypercapnic stimulation may provide a novel impact on sports training. We have recently demonstrated the physiological responses during exercise under hypercapnic condition (Kato et al. 2005, 2006, 2007). However, there is no study to address the effect of hypercapnic stimulation on sports training. Thus, the purpose of this study was to investigate the effect of hypercapnic stimulation on sports training, and we tested the intermittent hypercapnia (IHC) on ventilatory response in endurance athletes. Materials and methods: Six male and one female triathletes volunteered to participate in the present study. As an IHC, each subject performed hypercapnic gas (21%O2, 3%CO2, N2=balance) inhalation for one hour each day for two weeks. Hypercapnic ventilatory response (HCVR) and hypoxic ventilatory response (HVR) were determined four times in each subject; 1) before IHC; 2) after one week of IHC; 3) after two weeks of IHC; 4) one week after the cessation of IHC. The maximal exercise performance test was also carried out before and after IHC. Results: HCVR and HVR did not significantly change throughout the experiment period. On the maximal exercise test, maximal minute ventilation tended to increase from 146.0 ± 29.0 l/min to 155.4 ± 34.2 l/min by IHC (P = 0.059). But maximal workload (255.7 ± 36.4 W vs. 255.7 ± 40.4 W), exercise performance (891 ± 109 sec vs. 904 ± 130 sec), VO2max (58.9 ± 7.4 ml/kg/min vs. 60.9 ± 8.1 ml/kg/min), maximal respiratory rate (67.9 ± 17.8 f/min vs. 71.7 ± 21.3 f/min), and maximal heart rate (188.3 ± 8.7 beats/min vs. 189.1 ± 8.2 beats/min) did not differ between before and after IHC. Conclusion: Our present results suggested that IHC for two weeks may promote ventilation capacity, but could not lead to the change in HCVR and HVR.